2020
DOI: 10.1002/glia.23937
|View full text |Cite
|
Sign up to set email alerts
|

Cuprizone‐induced demyelination triggers a CD8‐pronounced T cell recruitment

Abstract: The loss of myelinating oligodendrocytes is a key characteristic of many neurological diseases, including Multiple Sclerosis (MS). In progressive MS, where effective treatment options are limited, peripheral immune cells can be found at the site of demyelination and are suggested to play a functional role during disease progression. In this study, we hypothesize that metabolic oligodendrocyte injury, caused by feeding the copper chelator cuprizone, is a potent trigger for peripheral immune cell recruitment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…Preliminary data suggest the presence of CD4+ and CD8+ T cells in the spinal cord and brain of ALS [ 19 ] and T cell subset alterations in the peripheral blood of ALS patients [ 20 , 21 , 22 ]. The presence of adaptive immune cells in the CNS of ALS patients is in line with the idea that a brain-intrinsic degenerative process can trigger the recruitment of peripheral immune cells [ 23 , 24 , 25 , 26 , 27 ]. Interestingly, recent studies provide evidence of the relevant role of T helper (Th)17 cells and their activation, both in animal models and patients with ALS [ 22 , 28 ].…”
Section: Introductionsupporting
confidence: 69%
“…Preliminary data suggest the presence of CD4+ and CD8+ T cells in the spinal cord and brain of ALS [ 19 ] and T cell subset alterations in the peripheral blood of ALS patients [ 20 , 21 , 22 ]. The presence of adaptive immune cells in the CNS of ALS patients is in line with the idea that a brain-intrinsic degenerative process can trigger the recruitment of peripheral immune cells [ 23 , 24 , 25 , 26 , 27 ]. Interestingly, recent studies provide evidence of the relevant role of T helper (Th)17 cells and their activation, both in animal models and patients with ALS [ 22 , 28 ].…”
Section: Introductionsupporting
confidence: 69%
“…In a recent study, we were able to show that, during the course of acute cuprizoneinduced demyelination, the recruitment of lymphocytes can be observed [76]. Interestingly, in contrast to most EAE models where inflammatory infiltrates are dominated by CD4 + T-cells [77], CD8 + cytotoxic T-cells outnumbered CD4 + T-helper cells.…”
Section: Does a Degenerative Process In The Cns Trigger Autoimmunity?mentioning
confidence: 83%
“…It is currently unclear, whether in MS such myelin abnormalities are induced by peripheral immune cells, can trigger or promote autoimmunity or promote the recruitment of peripheral immune cells. On the one hand, myelin vacuoles were found in the NAWM of MS patient material, where T cell densities are low (Kaddatz et al, 2021), suggesting that myelin disintegration might be an early event during MS lesion formation. On the other hand, similar abnormalities (i.e., myelinosomes) have been described in the autoimmune MS model EAE (Romanelli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We and others recently demonstrated that metabolic oligodendrocyte stress, induced by intoxication with the mitochondrial toxin cuprizone, results in myelin basic protein (MBP) citrullination which triggers autoimmune inflammatory demyelination (Scheld et al, 2016;Caprariello et al, 2018;Kaddatz et al, 2021). The ultrastructure of the myelin-axonal unit in the cuprizone model has been described in early works, demonstrating swellings of the inner tongue of the myelin sheath similar to the observed myelin detachments in MS and the EAE model (Blakemore, 1973;Ludwin and Johnson, 1981).…”
Section: Introductionmentioning
confidence: 86%